An approach to the history of the Cienfuegos Subsidiary of the Cuban Society of Clinical Pathology - Pedro Sánchez Frenes; Orietta Mediaceja Vicente; Dayamí García Torres; María de Jesús Sánchez Bouza; Pedro Javier Sánchez Sánchez; Martina Jiménez Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
A historical research is presented about the foundation and evolution of the Cuban subsidiary of clinical pathology in Cienfuegos, contextualized in antecedents, development and present situation of the clinical laboratories in the province. The most complex and important tasks which were developed by the members of the scientific society from its foundation to the current period are stated, so as future challenges.